2022
DOI: 10.1186/s13287-022-03156-9
|View full text |Cite
|
Sign up to set email alerts
|

Translational development of ABCB5+ dermal mesenchymal stem cells for therapeutic induction of angiogenesis in non-healing diabetic foot ulcers

Abstract: Background While rapid healing of diabetic foot ulcers (DFUs) is highly desirable to avoid infections, amputations and life-threatening complications, DFUs often respond poorly to standard treatment. GMP-manufactured skin-derived ABCB5+ mesenchymal stem cells (MSCs) might provide a new adjunctive DFU treatment, based on their remarkable skin wound homing and engraftment potential, their ability to adaptively respond to inflammatory signals, and their wound healing-promoting efficacy in mouse wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 106 publications
(144 reference statements)
0
29
0
1
Order By: Relevance
“…The use of autologous MSCs in clinical studies on diabetic CLTI patients have shown significant improvement in rates of overall wound healing (60,77). Lu et al have shown that over a longer period limb amputation rates were lower in the BM-MSC group compared to the BM-MNC group, and the ulcer recurrence rate in the BM-MSC group (29). Future studies should also examine similar MSC-based applications in CLTI patients with DM to ascertain whether similar beneficial effects for patients with DFU can be more broadly applied.…”
Section: Investigations Into Clti Patients With Concomitant Diabetic ...mentioning
confidence: 99%
See 3 more Smart Citations
“…The use of autologous MSCs in clinical studies on diabetic CLTI patients have shown significant improvement in rates of overall wound healing (60,77). Lu et al have shown that over a longer period limb amputation rates were lower in the BM-MSC group compared to the BM-MNC group, and the ulcer recurrence rate in the BM-MSC group (29). Future studies should also examine similar MSC-based applications in CLTI patients with DM to ascertain whether similar beneficial effects for patients with DFU can be more broadly applied.…”
Section: Investigations Into Clti Patients With Concomitant Diabetic ...mentioning
confidence: 99%
“…Treatment with gene-edited MSCs augmented blood perfusion and prevented limb loss in a murine model of hindlimb ischemia compared to unmodified MSCs due to the enhanced proangiogenic milieu induced by GCP-2 and SDF-1α-mediated upregulation of factors such as Angiopoietin 1 (Ang1) and VEGF ( 28 ). Kerstan et al utilized hypoxic incubation of skin-derived MSCs to induce upregulation of the transcription factor hypoxia-inducible transcription factor 1α (HIF-1α) ( 29 ). This further engaged canonical VEGF and angiogenic signaling pathways among MSCs to enhance capillary proliferation and vascularization in the ischemic muscle tissue of mice with hindlimb ischemia ( 29 ).…”
Section: Preclinical Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…MSCs have been frequently used and examined in clinic. For skin wound treatment, a series of clinical trials were performed to evaluate the efficacy of MSC application in serious skin burns ( Falanga et al, 2007 ), non-healing ulcers ( Dash et al, 2009 ; Li et al, 2013 ; Chen et al, 2018a ; Lu et al, 2019 ; Moon et al, 2019 ; Kerstan et al, 2021 ; Zhang et al, 2022a ; Kerstan et al, 2022 ) and advanced limb ischemia ( Yang et al, 2013 ; Lu et al, 2019 ). For example, Sheng et al first reported successful employment of MSCs to realize the regeneration of functional sweat glands in patients with deep burn injury ( Sheng et al, 2009 ).…”
Section: Biological Characteristics and Clinical Applications Of Mscsmentioning
confidence: 99%